Hubungan Pengetahuan tentang Kesehatan Gigi dan Mulut dengan Oral Hygiene Index Siswa Kelas V Sekolah Dasar Negeri Bulukantil Kecamatan Jebres - NILAM HESTI ARIYANI; Yulidar Hafidh; Suhanantyo . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2012)
Background: The issue of oral health in the community caused by behavioral factors or neglect of oral hygiene. It was based on lack of knowledge about the importance of maintaining oral health. This study aims to determine the relationship between knowledge of oral health with the Oral Hygiene Index of V Grade students in Bulukantil Elementary School District Jebres by controlling the confounding factors, the students tooth brushing habit. Methods: This study was an observational analytical research using cross sectional approach. Sample was taken by purposive sampling technique. Total samples were 48 students in V grade of Bulukantil Elementary School. Data were processed by SPSS 17.00 for Windows. Analysis of data was Chi-Square which Confidence Interval (CI) 95%. Results: There was no relationship between knowledge of oral health with the Oral Hygiene Index of V grade students in Bulukantil Elementary School District Jebres (p = 0.927). But, there was a significant relationship between tooth brushing habits with Oral Hygiene Index (p = 0.004). Conclusions: There was no relationship between knowledge of oral health with the Oral Hygiene Index of V grade students in Bulukantil Elementary School District Jebres. Key words: oral health knowledge, Oral Hygiene Index